磷脂在蛋白质乳液中的作用研究进展Research progress on the role of phospholipids in protein-based emulsions - 李雪阳1，邹依彤1，涂向辉1，祁冰洁1，刘新2， 杨庆余1，王丽娟1 " LI Xueyang1, ZOU Yitong1, TU Xianghui1, QI Bingjie1, LIU Xin2 , YANG Qingyu1，WANG Lijuan1" (Zhongguo youzhi)
蛋白质作为天然乳化剂对环境变化敏感，磷脂与蛋白质的相互作用可降低蛋白质对环境变化的敏感性。旨在为利用蛋白质、磷脂的优势共同提高乳液的稳定性，拓宽乳液工业应用提供参考，综述了不同蛋白与不同磷脂的相互作用、蛋白质与磷脂相互作用的影响因素以及蛋白质-磷脂复合乳液的应用。磷脂与蛋白质之间通过疏水相互作用使蛋白质乳液表现出更强的稳定性。蛋白质与磷脂相互作用的影响因素有磷脂与蛋白的比例、pH、温度、盐浓度和制备乳液所使用的物理手段（如高压、超声）。蛋白质-磷脂复合乳液可用于递送生物活性物质、制备低脂食品和人工乳。蛋白质-磷脂复合乳液能够应用于对稳定性要求高的食品中，为食品工业开发绿色稳定的乳化剂提供了新途径。 Proteins, as natural emulsifiers, are sensitive to environmental changes, and phospholipid-protein interactions can reduce the sensitivity of proteins to environmental changes. In order to provide a reference for using the advantages of proteins and phospholipids to jointly improve the stability of emulsions and broaden the industrial application of emulsions, the interaction between different proteins and different phospholipids, the influencing factors of the interaction between proteins and phospholipids, and the application of protein-phospholipid complex emulsions were reviewed. Through hydrophobic interactions between phospholipids and proteins, the protein emulsion shows a stronger stability. The factors influencing the interactions between proteins and phospholipids are the ratio of phospholipids to proteins, pH, temperature, salt concentration, and the physical means used to prepare the emulsions (e.g. , high pressure, ultrasound). Protein-phospholipid complex emulsions can be used to deliver bioactive substances, prepare low-fat foods and artificial milk. Protein-phospholipid complex emulsions can be applied to food with high stability requirements, which can provide a new way to develop green and stable emulsifier for the food industry.